1988
DOI: 10.1161/01.atv.8.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate changes in levels of human serum low and high density lipoprotein subclasses in healthy men.

Abstract: Measurement of serum lipoproteins by analytic ultracentrifugation revealed significant correlations involving subfractions of low density (LDL) and high density (HDL) lipoproteins in 81 men studied cross-sectionally at baseline and longitudinally during a 1-year exercise trial. One-year changes in lipoprotein levels in 38 exercising men and in 30 sedentary controls showed correlations that paralleled those observed at baseline. Positive correlations observed between plasma levels of larger, more buoyant LDL of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 17 publications
4
19
0
Order By: Relevance
“…Numerous studies have demonstrated strong correlations of plasma triglycerides and VLDL levels with increasing density and decreasing size of the predominant LDL subspecies (9,69,75). This may be related in part to the pathway relating VLDL to LDL heterogeneity shown in Fig.…”
Section: Role Of Plasma Lipase Activities In Production Of Ldl From Tmentioning
confidence: 85%
See 2 more Smart Citations
“…Numerous studies have demonstrated strong correlations of plasma triglycerides and VLDL levels with increasing density and decreasing size of the predominant LDL subspecies (9,69,75). This may be related in part to the pathway relating VLDL to LDL heterogeneity shown in Fig.…”
Section: Role Of Plasma Lipase Activities In Production Of Ldl From Tmentioning
confidence: 85%
“…1 is based on previously described reciprocal relationships involving their proposed lipolytic products LDL-III and LDL-I, respectively ( Fig. 2 ) (69). Similarly, based on reciprocal relationships between LDL II and LDL IV (Fig.…”
Section: Metabolic Influences On Ldl Heterogeneitymentioning
confidence: 97%
See 1 more Smart Citation
“…In morbidly obese women who underwent gastric bypass surgery 15 there was an increase in LDL size and a decrease in LDL density after weight loss. In a study that examined the effects of exercise on lipoprotein lipids, neither HDL-C levels nor 45 presumably because many of the subjects failed to achieve a sufficient level of training. However, there were significant correlations between changes in LDL flotation rates and changes in TG and HDL levels and an inverse relation between changes in the buoyant LDL-I and dense LDL-III subclasses.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the assumptions concerning these pathways, many studies have shown a strong correlation of plasma triglycerides and the levels of very low-density lipoproteins with an increase in density as well as a decrease in size of the predominant LDL subspecies [13][14][15].…”
Section: Lipoprotein Subfractionsmentioning
confidence: 60%